Daniel Stern: Microanalysis and the Empirical Infant Research Foundations. Issue 4 (19th May 2017) - Beebe, Beatrice
ABSTRACT: Daniel Stern changed the face of psychoanalysis, as well as that of infant research. He was a brilliant, innovative, and playful thinker. Psychoanalysis particularly values his contributions on the relevance of infant research to adult clinical practice and theory, for which he is best known. But this work has its foundation in his early empirical infant research, which is less well known. I believe that a better appreciation of the original empirical basis of his work using microanalysis will deepen our appreciation of his later thinking. In this article I return to the beginning of his work, using frame-by-frame microanalysis of film and, particularly, his first paper published in 1971. I sketch out some of the important findings and ideas emerging from this paper that continued to influence his thinking throughout his career. This research was conducted in the 1970s, the period in which I worked with him directly.